2011
DOI: 10.1186/1749-8546-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-infectious effects of Evodia rutaecarpa (Wuzhuyu) and its major bioactive components

Abstract: This article reviews the anti-inflammatory relative and anti-infectious effects of Evodia rutaecarpa and its major bioactive components and the involvement of the nitric oxide synthases, cyclooxygenase, NADPH oxidase, nuclear factor kappa B, hypoxia-inducible factor 1 alpha, reactive oxygen species, prostaglandins, tumor necrosis factor, LIGHT, amyloid protein and orexigenic neuropeptides. Their potential applications for the treatment of endotoxaemia, obesity, diabetes, Alzheimer's disease and their uses as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 94 publications
(97 reference statements)
1
44
0
1
Order By: Relevance
“…Fifteen microliter (15 μl) reaction containing 0.5 μl single-strand cDNA, 7.5 μl Master Mix, 1 μl of the each forward and reverse primers (5 pmol/μl) and 5 μl dH 2 O. The primers forABCG5 and β-actin (as normalizer) were taken from Hongwei et al, 2003 and Gao &Yuan, 2010, respectively) (Table 1) (34, 35). Real-time PCR reactions were performed using the Rotor Gene 3000 real time PCR system from Corbett using following program: step1: 95°C for 5 min and step 2: 40 cycle of 95°C for 10 sec and 60°C for 30 sec.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen microliter (15 μl) reaction containing 0.5 μl single-strand cDNA, 7.5 μl Master Mix, 1 μl of the each forward and reverse primers (5 pmol/μl) and 5 μl dH 2 O. The primers forABCG5 and β-actin (as normalizer) were taken from Hongwei et al, 2003 and Gao &Yuan, 2010, respectively) (Table 1) (34, 35). Real-time PCR reactions were performed using the Rotor Gene 3000 real time PCR system from Corbett using following program: step1: 95°C for 5 min and step 2: 40 cycle of 95°C for 10 sec and 60°C for 30 sec.…”
Section: Methodsmentioning
confidence: 99%
“…Aldose reductase inhibitors have considerable potential in treatment of diabetic complications, without increased risk of hypoglycemia (Kato et al, 2009). Evodiamine improved glucose tolerance and prevented the progress of insulin resistance associated with obese/diabetic states through inhibition of mTOR-S6K signaling and IRS1 serine phosphorylation in adipocytes (Liao et al, 2011;Wang et al, 2013). Rutaecarpine, an indolopyridoquinazoline alkaloid, isolated from E. rutaecarpa showed potential effects on diabetic metabolic syndrome (Jia and Hu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Evodiamine and rutaecarpine are the primary bioactive ingredients in E. rutaecarpa , and were designated as the biomarkers for quality evaluation of this herb medicine (Chinese Pharmacopoeia Committee, ). It has been found that evodiamine has anti‐inflammatory (Liao, Chiou, Shen, Wang, & Chen, ), anti‐obesity (Kobayashi et al, ) and vasodilatory effects (Chiou, Liao, & Chen, ). Recent studies have proved that evodiamine shows cytotoxicity on various human cancer cell lines (Adams et al, ; Liao et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%